Easy buying and selling through mytrustedbazaar platform: a conceptual solution - Ahmad Dahlan, Abdul Rahman; Jafre, Nur Hidayah; Ahmad Salhi, Nabilah; Ramlan, Nurul Akmam (Eclat Research Publication, 2015)
This paper proposed a one-stop service platform named MyTrustedBazaar. This trusted platform is for Muslims to sell and buy variety of quality products at affordable price. This system has the ability to categories product accordance to products types which more users friendly for Muslims to do online buying and selling. This system provides a platform for advertising buying and selling goods only, whereas the process of transaction occurs outside this system.